The Failure Mechanism and Control Technology of Coal Wall of a Large Mining Height Panel - Jaichen Wang; Shengli Yang; Dezhong Kong (International Conference on Ground Control in Mining, 2015)
"The stability control of longwall coal face is the key technology of large-cutting-height mining method. Therefore, a systematic study of the factors that affect coal face stability and its control technology is required in the development of large-cutting-height mining method in China. After the practical field observation and years of study, it was found that the more than 95% of failure in coal face are shear failure. The shear failure analysis model of coal face has been established, that can perform systematic study among factors such as mining height, coal mass strength, roof load, support resistance, and face flipper protecting plate horizontal force. Meanwhile, sensitivity analysis of factors influencing coal face stability showed that improving support capacity, cohesion of coal mass and decreasing roof load of coal face are the key to improve coal face stability. Numerical simulation of the factors affecting coal face stability has been performed using UDEC software and the results are consistent with the theoretical analysis. The coal face reinforcement technology of largecutting- height mining method using the grouting combined with coir rope is presented. Laboratory tests have been carried out to verify its reinforcement effect and practical application has been implemented in several coal mines with good results. It has now become the main technology to reduce longwall coal face failure of large-cutting-height mining method.INTRODUCTIONLarge-cutting-height mining method of more than 3.5m mining height, is one of the main methods for thick-seam mining in China. Currently, the largest mining height is 7.3m and the support capacity is 1,800mt. Shendong and Jincheng mining area have the best use of large-cutting-height mining technology (Wang, 2009). Generally, the mining height ranges from 6.5m to 7m and the support capacity ranges from 1,000mt to 2,000mt, annual output of the panel is between 10 and 12 million tons and the highest are 15 million tons. The main goal of large-cutting-height mining technology is to achieve high yield and high efficiency by increasing the advancing speed of longwall face (Yuan, 2011- 2012). However, in certain geologic conditions, rib spalling and roof falls in the unsupported area often occur. Because of the large tonnage of large-cutting-height mining equipment, once the rib spalling and roof falls cause the equipment to be out of alignment, the face advancing speed could be affected seriously that in turn affects the output (Yang, 2012). Therefore, studying the failure mechanism and control technique of coal face in large-cuttingheight mining method is of great significance."